Endophytic Fungi Isolated from the Marine Macroalga Dictyopteris pacifica in Korea - Ji-Won Kim; Yun-Jeong Kim; Ahn-Heum Eom (Mycobiology)
The exploration of endophytic fungi associated with seaweeds has garnered significant interest due to their crucial ecological functions and potential as sources of valuable bioactive compounds. In this study, we isolated and identified endophytic fungi from the brown seaweed Dictyopteris pacifica, collected from the intertidal zone of Yeongdoek, Gyeongsangbuk-do in Korea. Through morphological examination and molecular phylogenetic analysis using multiple molecular markers, including ITS, LSU, SSU, TEF1, TUB2, and RPB2 sequences, we identified three fungal species not previously recorded in Korea: Emericellopsis fuci, Neoarthrinium lithocarpicola, and Periconia chimonanthi. Detailed descriptions of morphological characteristics and phylogenetic analyses are provided. This study represents the first report of these endophytic fungi isolated from D. pacifica in Korea, thereby enhancing the understanding of the diversity of seaweed-associated endophytic fungi in the region.